Die veelvuldige rolle van 'n aantal beroepsvroue in die Vrystaat-streek : 'n Gevallestudie - Maasdorp, Colette (Bloemfontein: Central University of Technology, Free State, 2004)
With the entry of ever-greater numbers of women to the labour market and management positions, there is a considerable increase in the number of career women striving to make a success of their career, as well as their domestic and . family responsibilities. It is therefore essential that the multiple roles fulfilled by the career woman are investigated. Consequently, a study was undertaken with the following aim: To investigate the nature of, the relationships between, and the impact of various factors on the career woman in the household and at management level in the Free State banking sector. The factors referred to include the support framework within and outside the home, as well as modem aspects such as stress, conflict and equity within her workplace and management role. A literature study of relevant sources concerning the career woman in multiple roles was undertaken in an effort to gain insight into: the career woman and the working environment, the problems she experiences in her working environment, and her overall acceptance in a management position, as well as the career woman's role in the household and the support she receives. The target group is all women in management positions with ABSA in the Free State region. The women who participated in the research were occupying top-, middle- or lower-level management positions (supervisors). Emanating from the results and conclusions are the following recommendations: o An investigation should be launched into the organisational structure of ABSA. It is recommended that the team be limited to eight to ten subordinates per line manager. Such a move might serve to enhance the productivity of the division (unit) and reduce the workload of the manager. o Since the most prevalent cause of conflict is a clash of personalities, it is recommended that staff receive training in how to identify and deal with different personality types. o ABSA can also help to reduce worklfamily conflict by taking the following aspects into consideration: the term of employment; the availability of services to family members; the short-term care of ill family members; and the degree to which family considerations are recognised in the workplace. o Attention must be given to the chief causes of stress (namely, an excessive workload, a changing working environment, pressure for recognition in the workplace, and interpersonal relationships), since these have a significant influence in the stress levels of respondents. The changing culture of longer working hours has a negative impact on home life, and therefore management must make an effort to promote the importance of a balance between work and home life. o Women should be motivated and incentives should be instituted to ensure that staff improves their qualifications. Investing in human capital benefits not only the individual, but also the business. o Most of the respondents employed at the provincial head office, the Brandwag branch in Bloemfontein and the Maitland Street branch in Bloemfontein would prefer a childcare facility on the premises at which they are employed. As a test run, consideration could be given to a childcare facility on the premises of the provincial head office or the Brandwag branch in Bloemfontein, since these two Bloemfontein branches are situated alongside each other. In this way, a single childcare facility could accommodate the children of both branches' employees. o Children should be taught from a young age to be helpful. Even small -children can perform certain tasks in the home in order to cultivate a sense of responsibility. o Respondents should attend courses that will teach them to identify and deal with the demands a career places on family life. Possible courses in this respect include: time management, stress management, and wellness awareness courses. o Every career woman must practise effective time management. Training courses and seminars are recommended in an effort to teach effective time management - not only in the working environment, but also at home. o A formal policy on flexitime needs to be instituted in consultation with employees. Such a policy would afford career women the opportunity to lend greater support to their children and spouses without negatively affecting their employers.
Thesis
Keywords: Career women - Free State (South Africa); Working mothers - Job stress; Job stress